The Influence of Job Rotation and Communication on Job Performance at the Bogor Customs and Excise Supervision and Service Office - Kabul, Eka Rakhmat; Madiistriyatno, Harries; Sulistiono, Heru (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to analyze the effect of work rotation and communication on work performance at the Bogor Customs and Excise Supervision and Services Office. Job rotation is a human resource management strategy used to develop employee skills and increase work motivation through moving employees between job posts. Communication, both vertical and horizontal, plays an important role in maintaining the efficient flow of information and building harmonious working relationships. This research uses quantitative methods with a survey approach. The research results show that work rotation and communication have a positive and significant effect on employee work performance, either partially or simultaneously. These two variables together make a big contribution to increasing employee work performance in the Bogor Customs and Excise office environment. These findings show the importance of implementing planned and effective work rotation, as well as good communication management to improve employee performance. The practical implication of this research is that organizations can consider improving job rotation programs and strengthening internal communication systems to achieve operational and strategic goals.